Effect of Aromatherapy on Sleep Quality: A Systematic Review - Salamung, Niswa; Elmiyanti, Ni Ketut (Alta Dharma Publisher, 2023)
Background: Sleep disorders, commonly known as insomnia, are a risk factor that often occurs in chronic diseases, diabetes mellitus, hypertension, cardiovascular and obesity. The prevalence results of sleep disorders from countries worldwide ranged from 1.6% to 56.0%. The purpose of this systematic review is to analyze the effect of aromatherapy on sleep quality. Methods: a systematic review was applied in this study. Five databases are used: PubMed, Science Direct, Scholar, SAGE, and ProQuest. The article search starts in August – October 2022. Results: From 15 journals consisted of 12 randomized controlled trials (RCT) journals and three quasi-experimental journals. All studies are published in English, and the year of publication is 2017 – 2022. The methods used in providing the intervention are inhalation aromatherapy (10 articles), aromatherapy massage (4 articles), and a combination of both inhalation-massage (1 article). Aromatherapy is used, among others, lavender, peppermint, rosa damascene, tea tree oil, chamomile, and orange. Conclusion: Statistically, the effect of essential aromatherapy on sleep quality was significant. The effect of aromatherapy has an impact on improving sleep quality in adults, the elderly, and those with particular problems such as cancer, heart disease, hemodialysis, burns, ICU patients, and prediabetics. Recommendation: For future research, it is recommended to focus more on comparing the effectiveness of using aromatherapy between massage and inhalation in dealing with sleep quality